Analysis of Factors Affecting Compliance Taking Medicine for Elderly Hypertension Based Health Belief Models - Pristianti, Aulia Hilda; Vitaliati, Trisna; Maurida, Nurul (Al-Hijrah Indonesia, 2023)
Entering old age, more and more diseases attack the elderly, including high blood pressure. Most people with hypertension don't know they have hypertension because it has no symptoms, so it's often called the silent killer. Elderly people must adhere to treatment in cases of hypertension, especially by taking antihypertensive drugs. The problem faced by elderly people with hypertension is that most of them do not adhere to their medication. The behavior of following a doctor's advice comes from beliefs or perceptions. The health belief model is one of the theories based on faith. This study aimed to analyze the factors affecting medication adherence in the elderly with hypertension as a function of health belief regimen. This study uses a type of quantitative research. The study design used descriptive analysis with a cross-sectional design. The study population consisted of 107 elderly people with a sample of 100 elderly people with hypertension in the work area of Jenggawah Primary Health Center. The study will be conducted from April to May 2023. The instrument used in the study is a questionnaire. Based on the test results by SPSS using a logistic regression test with α of 0.05, perceived susceptibility p-value of 0.003, p-value of perceived severity of 0.036, p-value of perceived benefit is 0.682 observed, perceived barriers are found to be p-value 0.216, self-efficacy p value 0.081, cues to action p value 0.746. Based on the study results, it can be concluded that there is an influence of the perception of susceptibility and the perception of severity on the adherence to drug treatment in the elderly with hypertension.